CONCEPTUAL BASES OF THE ENERGY EFFICIENT SYSTEM OF MANAGEMENT OF COMBINED UNITS OF WASTEWATER TREATMENT - V. N. Shtepa (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2016)
A critical analysis of the shortcomings of the existing water purification systems is conducted. In order to ensure environmental safety and energy savings it is proposed to use the combined units, including physical, chemical, physical-and-chemical and biological methods. The attention is driven to the fact that the most effective way to maintain current water purification is an adaptive control system. The shortcomings of the management of water treatment units were revealed and it was proposed to produce their synthesis based on the mathematical apparatus of artificial intelligence systems. Taking into account the requirements of the environmental safety and the need in the energy savings, the energy efficiency criteria of combined system functioning has been developed. At an industrial plant (slaughterhouse wastewater treatment) the compliance of the production conditions of the criterion has been undertaken that confirmed the criterion relevance and usefulness as applied to the synthesis of energy-efficient control systems. A synthetic control system combined the water treatment plants. Having based on the preliminary research and analysis of the current work in the subject area the architecture of a control system of combined water treatment units that use intelligent technology was developed. The key functional of the unit – information-analytical subsystem of the formation control actions including: multilayer perceptrons self-organization Kohonen network, fuzzy cognitive map. The basic difference between the developed design and its analogues is the ability to adjust the settings of equipment adaptively on the basis of processing sensor data, information on the price of consumables, volley discharges of pollutants, a sudden change in the flow and other force majeure. Adjustment of the parameters of the control system is carried out with the use of experimental and analytical data stored in the knowledge base of technological processes.